PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH DALAM MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SDN BANJARSARI 01 KABUPATEN MADIUN TAHUN PELAJARAN 2015/2016 - Harsanti, Arni Gemilang (Universitas Muhammadiyah Semarang, 2017)
Low student learning outcomes to social studies is a problem that often arises in social studies learning. This is because the learning model still did not agree with the teaching objectives. Learning through learning model is expected to make a match the students' understanding and absorption of the material being taught can be achieved more quickly. Through this learning teachers deliver structured learning materials related to real life in the hope of the subject matter presented can be controlled by the student well and create a pleasant learning environment for students. This study aims to determine whether the implementation of cooperative learning model make a match in improving student learning outcomes in social studies teaching and learning activities in the classroom. This research is a classroom action research (PTK), which is carried out in three cycles of study with the matter